The power to resist: irrigation management transfer in Indonesia - Suhardiman, Diana (2013)
In the last two decades, international donors have promoted Irrigation Management Transfer (IMT) as an international remedy to management problems in government irrigation systems in many developing countries. This article analyses the political processes that shape IMT policy formulation and implementation in Indonesia. It links IMT with the issue of bureaucratic reform and argues that its potential to address current problems in government irrigation systems cannot be achieved if the irrigation agency is not convinced about the need for management transfer. IMT's significance cannot be measured only through IMT outcomes and impacts, without linking these with how the irrigation agency perceives the idea of management transfer in the first place, how this perception (re)defines the agency's position in IMT, and how it shapes the agency's action and strategy in the policy formulation and implementation. I illustrate how the irrigation agency contested the idea of management transfer by referring to IMT policy adoption in 1987 and its renewal in 1999. The article concludes that for management transfer to be meaningful it is pertinent that the issue of bureaucratic reform is incorporated into current policy discussions.